Bounded Rationality, Disinformation, and Infodemic in COVID-19 Times - Antonio Roazzi; Ana Iza G. Sobral; Alanny Nunes de Santana; Nathália Patrícia T. B. de Melo; Robson Savoldi; Rodrigo Édipo do Nascimento Silva (Psicologia: Teoria e Pesquisa)
Abstract Infodemic is defined by excessive content of different qualities associated with a specific subject and has relevant consequences. The COVID-19 pandemic is unprecedented, exacerbating the search for information and creating some risks, including not recognizing the veracity and quality of the disseminated content. In this context, this study reflects on the pandemic phenomenon and its psychosocial impacts from the cognitive perspective of limited rationality, understanding the excess of information through decision-making based on heuristics. It is challenging and undeniable that it is up to the authorities to combat and reduce the spread of Infodemic.